Interview: Adapting to the changing field of imaging. (August 2013) - Krestin, Gabriel
Gabriel Krestin talks to Natasha Galukande, Assistant Commissioning Editor. Krestin graduated from the Faculty of Medicine at the University of Cologne (Germany) in 1981 and completed a residency in radiology in 1988 before completing his PhD in 1989. Krestin then worked as a radiologist and head of the MRI center at the Department of Radiology, University Hospital in Zurich (Switzerland) before becoming Chairman in the Department of Radiology at Erasmus Medical Center, University Medical Centre Rotterdam (The Netherlands). Krestin is an active member of many national and international societies and has just completed a 1-year presidency of the European Society of Radiology, where he is still on the executive committee and a chair member. He has authored over 350 original articles and 60 book chapters, in addition to serving on the editorial board of several international journals, including Imaging in Medicine .